UV-mediated tuning of surface biorepulsivity in aqueous environment - Weber, Theresa; Meyerbröker, Nikolaus; Khan Hira, Md. Nuruzzaman; Zharnikov, Michael; Terfort, Andreas (Chemical communications, 2014)
While it is well-known that oligoethylene glycol (OEG) terminated self-assembled monolayers (SAMs) can be deteriorated by UV irradiation in air, we now report that the analogous modification can also be performed in water, opening the opportunity for in situ tuning of biorepulsive properties. Surprisingly, this deterioration also takes place even in the absence of molecular oxygen, resulting in a very selective process.